2019
DOI: 10.1093/cid/ciz841
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hepatitis B Infection and Immunity Among Women of Childbearing Age in the United States

Abstract: Background The current opioid injection drug use epidemic has been associated with an increase in hepatitis C virus infections among women of childbearing age in the United States, but changes in hepatitis B virus (HBV) infections have not been studied. Methods A retrospective analysis of HBV statuses among women of childbearing age nationally and by state was conducted, utilizing the Quest Diagnostics database. Rates of HBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The national prevalence of new, chronic HB diagnoses among women of childbearing age in US decreased significantly from .83% in 2011 to .19% in 2017. 25 In the present study, we observed that 3 out of 91 subjects were born to HBsAg-positive mothers and received hepatitis B immunoglobulin (HBIG) and HB vaccine at the day of birth. They were all born in US.…”
Section: Discussionmentioning
confidence: 82%
“…The national prevalence of new, chronic HB diagnoses among women of childbearing age in US decreased significantly from .83% in 2011 to .19% in 2017. 25 In the present study, we observed that 3 out of 91 subjects were born to HBsAg-positive mothers and received hepatitis B immunoglobulin (HBIG) and HB vaccine at the day of birth. They were all born in US.…”
Section: Discussionmentioning
confidence: 82%
“…A recent study using national data from Quest Laboratories found a significant increase in the number of reproductive age women in WV testing positive for anti-HBc, a marker of past or current HBV infection. 15 Although the odds of completing the series were highest among LHD family planning clinic participants, the number of women reached was relatively small compared with other settings. Future vaccination efforts should include screening LHD family planning participants for HBV risk factors.…”
Section: Discussionmentioning
confidence: 94%
“…In the Multicenter AIDS Cohort Study, a longitudinal cohort of men who have sex with men in the US, incident HBV infection was nearly 2-fold higher in HIV-infected MSM compared with HIV-uninfected MSM and ART was not found to be completely protective [42]. Nationally in the US, rates of HBV have risen in regions where opioid use has been prevalent [43]. HBV incidence has also been shown to be moderately high in HBV-endemic settings among PLWH with relatively preserved CD4 cell counts [44].…”
Section: Hbv Prevention With the Goal Of Eliminationmentioning
confidence: 99%